THE INFLUENCE OF CHANGE MANAGEMENT ON ORGANIZATIONAL DYNAMICS AND EMPLOYEE BEHAVIOR - Mitra, Sumit; Soni, Sandeep (ShodhKosh: Journal of Visual and Performing Arts, 2024)
For an organization to survive, it must constantly compete for scarce resources in a changing and dynamic environment. We don't just focus on change, we seek change. Transformation means a step from one form to another. The thought of replacing or changing strikes fear into people's hearts. If changes are not well communicated within an organization, it will be difficult to implement the changes into action. People see it as continuous change that requires adjustment or adjustment. Presented to an organization to make structural adjustments, programs, projects or solutions to improve performance. The research carried out shows the importance of change management communication in an organization, fundamental to the success of the organization. There are many change management factors such as personnel, leadership, training and development, compensation and recognition, culture, policy and information systems that affect the success of an organization and must be considered when planning the management of organizational change.